Habichuela mantequilla - Carulla, J. (International Center for Tropical Agriculture, 1987)
The characteristics of snap bean var. Mantequilla, currently available in the Colombian market and with better organoleptic and cooking characteristics than var. California, are described. Tables with data on the vol. of legumes commercialized at Corabastos (the wholesale central station) and Carulla (Bogota, Colombia) in 1985- 86 and 1986, resp., are included. Requirements and specific organoleptic characteristics of snap beans in Carulla y Compania, S.A. are also presented as well as guidelines for purchasing, receiving, and selecting snap beans both at warehouses and supermarkets. (CIAT)